Real‐world data on EGFR/ALK gene status and first‐line targeted therapy rate in newly diagnosed advanced non‐small cell lung cancer patients in Northern China: A prospective observational study. Issue 7 (29th May 2019) - Liang, Hongge; Song, Xia; Zhang, Yuhui; Zhang, Shucai; Li, Fang; Fang, Jian; Li, Junling; Liang, Li; Nie, Ligong; Ma, Kewei; Zhang, Liangming; Wang, Xiaohong; et al.
Abstract : Background: Tyrosine kinase inhibitors (TKIs) can significantly prolong overall survival for patients with advanced non‐small cell lung cancer (NSCLC) harboring epidermal growth factor receptor ( EGFR )‐mutation or anaplastic lymphoma kinase ( ALK )‐rearrangement. However, the real‐world evaluation status of ALK/EGFR in China remains unclear. Methods: We conducted a prospective study including 1134 patients with cytologically or histologically confirmed advanced NSCLC (stage IIIb–IV) at 12 Chinese hospitals. Results: The most common evaluation methods were amplification‐refractory mutation system for EGFR status and immunohistochemistry targeting D5F3 for ALK status. Among patients with non‐squamous, the EGFR mutation rate was 44.1% and the ALK rearrangement rate was 10.0%. Among patients with squamous cell carcinoma, the EGFR mutation rate was 8.3% and the ALK rearrangement rate was 3.7%. Among all patients, gender (HR = 1.7, 95%CI = 1.2–2.4, P = 0.006), smoking history (HR = 1.8, 95%CI = 1.3–2.7, P = 0.001), histology (HR = 5.0, 95%CI = 2.4–10.1, P < 0.001), and brain metastases (HR = 1.5, 95%CI = 1.1–2.2, P = 0.017) were independent predictors of EGFR mutation, while age (HR = 2.6, 95%CI = 1.7–4.1, P < 0.001) was an independent predictor of ALK rearrangement. The median time from tumor diagnosis to EGFR or ALK status confirmation was 7 and 5 days, respectively. Targeted therapy rate was 73.8% in EGFR ‐positive patients and 51.4% in ALK ‐positive patients. There was a negative correlation between the first‐line targeted therapy rate and the EGFR mutation detection period (r = −0.152, P = 0.02), while no significant correlation among patients with ALK rearrangement (r = −0.179, P = 0.076). Conclusion: Squamous NSCLC patients should also be routinely tested to determine their EGFR / ALK statuses. The first‐line targeted therapy rate remains low in Chinese patients with NSCLC.